Biodegradable polyester composition, preparation method thereof and biodegradable non-woven fabric
By using aliphatic-aromatic copolyesters A and B of different molecular weights, the problems of poor softness and high energy consumption of existing nonwovens are solved, and the produced nonwovens have excellent mechanical properties and reduced processing temperature.
Patent Information
- Application Number
- CN202311376616.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing biodegradable nonwoven fabrics have poor flexibility, low elasticity, and high processing temperature, resulting in increased energy consumption and failure to effectively utilize copolyesters of different molecular weights and compositions.
The biodegradable polyester composition is prepared by blending and extrusion processes such as aliphatic-aromatic copolyesters A and B of different molecular weights. The obtained nonwoven fabric has a soft touch, good ductility and excellent mechanical strength.
It realizes the soft touch, good ductility and excellent mechanical strength of non-woven fabrics. It is suitable for disposable sanitary products, sheets, filters and packaging bags, etc., reducing processing temperature and energy consumption.
Smart Images

Figure CN119875314A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials, and in particular, relates to a biodegradable polyester composition, a method for preparing the biodegradable polyester composition, and a biodegradable nonwoven fabric prepared from the biodegradable polyester composition. Background Art
[0002] Nonwoven fabrics, also known as non-woven fabrics, are a type of fabric that does not require spinning and weaving. The fibers are oriented or randomly arranged to form a fiber mesh structure, and then reinforced by mechanical, thermal bonding or chemical methods. Nonwoven fabrics are widely used in medical, sanitary, clothing, filtration, insulation, food packaging and agriculture. At present, with the continuous improvement of environmental protection standards, it has become a trend to use more environmentally friendly biodegradable plastics to replace traditional non-degradable plastics. Therefore, biodegradable nonwoven fabrics are a new type of product that has both practicality and sustainable development characteristics.
[0003] The main non-woven fabric processing methods currently available on the market are meltblowing and spunbond. Compared with meltblown fabrics, spunbond non-woven fabrics have greater breaking strength and elongation, can meet various performance requirements, and have reliable strength. The raw materials used to make biodegradable spunbond non-woven fabrics include polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), polybutylene succinate (PBS) and polycaprolactone (PCL). The performance of non-woven fabrics prepared from a single component often has some disadvantages, such as low bonding flexibility, high roughness, hard touch, poor texture and softness of non-woven fabrics prepared from a single PLA. In order to improve the above shortcomings, methods such as mixing, copolymerization or blending of different materials can be used.
[0004] Patent document CN102395720A provides a biodegradable spunbond nonwoven fabric, which is mixed with two degradable materials, one of which is PLA or PLA copolymer, and the other is PBS or PBS copolymer. Patent document CN101331257 discloses a spunbond nonwoven fabric mixed with PBS and PLA. Patent document CN1415027 provides a composition of PLA and polybutylene succinate and a spunbond nonwoven fabric thereof, which has good water absorption. However, PLA has a high glass transition temperature and a high melting point, and the resulting nonwoven fabric has poor softness and low elasticity, and the required processing temperature is also high, thereby increasing energy consumption. Patent document CN1478015 provides an aliphatic-aromatic copolyester spunbond nonwoven fabric, which has excellent drape, wrinkle resistance and elasticity.
[0005] In addition, none of the above prior arts involve the problem of using copolyesters with different molecular weights and different compositions together. This problem is of special significance to the field of degradable polyesters, because the molecular weight of degradable polyesters will decrease during storage, which will lead to their inability to meet the original demand. If they are properly utilized, it will reduce resource waste and have significant economic and social benefits. Summary of the invention
[0006] In order to improve the shortcomings of the prior art and further improve the utilization rate of biodegradable polyesters, the present invention provides a biodegradable polyester composition, a preparation method thereof and a biodegradable non-woven fabric. The two aliphatic-aromatic copolyesters in the composition have different molecular weights, which can realize the scientific utilization of materials with different molecular weights. The obtained non-woven fabric has a soft touch, good ductility, and excellent mechanical strength, and can be suitable for disposable sanitary products, sheets, filtration and various packaging bags.
[0007] The first aspect of the present invention provides a biodegradable polyester composition, which contains an aliphatic-aromatic copolyester A and an aliphatic-aromatic copolyester B, wherein the content of the aliphatic-aromatic copolyester A is 3-30% by weight, and the content of the aliphatic-aromatic copolyester B is 70-97% by weight, based on the total weight of the aliphatic-aromatic copolyester A and the aliphatic-aromatic copolyester B;
[0008] The aliphatic-aromatic copolyester A is a copolymer containing repeating units represented by formula (I) and (II);
[0009]
[0010]
[0011] In formula (I), m1=4, n1=2 or 4;
[0012] In the aliphatic-aromatic copolyester A, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 40-49 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester A is 35000 g / mol-65000 g / mol;
[0013] The aliphatic-aromatic copolyester B is a copolymer containing repeating units represented by formula (III) and (II);
[0014]
[0015] In formula (III), m2=4, n2=8;
[0016] In the aliphatic-aromatic copolyester B, based on the total molar number of repeating units represented by formula (III) and (II), the content of the repeating unit represented by formula (II) is 40-50 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester B is 95000 g / mol-120000 g / mol.
[0017] The second aspect of the present invention provides a method for preparing the above-mentioned biodegradable polyester composition, which comprises: blending the components of the composition to obtain a mixed material; extruding, cooling and pelletizing the mixed material to obtain the biodegradable polyester composition.
[0018] The third aspect of the present invention provides a biodegradable non-woven fabric, which is prepared by using the above-mentioned biodegradable polyester composition.
[0019] The non-woven fabric prepared by the composition of the present invention has uniform thickness, soft touch, good comprehensive mechanical properties, high elongation, good toughness, and certain rigidity, ensuring durability and strength, and good mechanical properties. The non-woven fabric raw material has good processability, a simple preparation method, and a stable structure during processing.
[0020] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0021] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0022] According to a first aspect of the present invention, the present invention provides a biodegradable polyester composition, the composition comprising an aliphatic-aromatic copolyester A and an aliphatic-aromatic copolyester B, wherein the content of the aliphatic-aromatic copolyester A is 3-30% by weight, and the content of the aliphatic-aromatic copolyester B is 70-97% by weight, based on the total weight of the aliphatic-aromatic copolyester A and the aliphatic-aromatic copolyester B;
[0023] The aliphatic-aromatic copolyester A is a copolymer containing repeating units represented by formula (I) and (II);
[0024]
[0025] In formula (I), m1=4, n1=2 or 4;
[0026] In the aliphatic-aromatic copolyester A, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 40-49 mol %; the weight average molecular weight of the aliphatic-aromatic copolyester A is 35000 g / mol-65000 g / mol;
[0027] The aliphatic-aromatic copolyester B is a copolymer containing repeating units represented by formula (III) and (II);
[0028]
[0029] In formula (III), m2=4, n2=8;
[0030] In the aliphatic-aromatic copolyester B, based on the total molar number of repeating units represented by formulas (III) and (II), the content of the repeating unit represented by formula (II) is 40-50 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester B is 95000 g / mol-120000 g / mol.
[0031] The composition of the present invention contains two aliphatic-aromatic copolyesters. The introduction of aromatic structural units ensures the strength of the non-woven fabric. Fat chains of different lengths give the non-woven fabric a certain flexibility. The touch and mechanical properties of the non-woven fabric can be adjusted by the blending ratio. The composition is easy to implement and has low cost.
[0032] Preferably, based on the total weight of aliphatic-aromatic copolyester A and aliphatic-aromatic copolyester B, the content of aliphatic-aromatic copolyester A is 10-25 wt %, and the content of aliphatic-aromatic copolyester B is 75-90 wt %.
[0033] Preferably, in the aliphatic-aromatic copolyester A, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 42-47 mol%.
[0034] Preferably, in the aliphatic-aromatic copolyester B, the content of the repeating unit represented by formula (II) is 44-49 mol %, based on the total molar number of the repeating units represented by formula (III) and (II).
[0035] In the present invention, the weight average molecular weight of the composition may be 88000-115000 g / mol.
[0036] According to the present invention, according to the performance requirements, the composition further contains an auxiliary agent, which includes but is not limited to an antioxidant, a chain extender, talcum powder, etc., and the amount added is the conventional amount in the art. The auxiliary agent can be various types conventionally used in the prior art. For example, the antioxidant can be a hindered phenol antioxidant, a phosphite antioxidant, a pentaerythritol ester antioxidant, etc.
[0037] In the present invention, aliphatic-aromatic copolyester A and aliphatic-aromatic copolyester B are random copolymers, and their sources are not particularly limited. They can be prepared by conventional means in the art or commercially available, as long as the above-mentioned parameter requirements are met. The copolyesters used in the embodiments of the present invention are prepared.
[0038] The aliphatic-aromatic copolyester A and the aliphatic-aromatic copolyester B in the present invention can be prepared by the following method, which specifically comprises the following steps:
[0039] (1) contacting a diacid, an ester thereof, an anhydride thereof or a mixture thereof, a diol, and a first catalyst in a reaction vessel under vacuum conditions and prepolymerizing the contacted diacid to obtain a prepolymer; the diacid refers to an organic dicarboxylic acid, such as terephthalic acid, succinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, etc.; the diol refers to butanediol;
[0040] (2) contacting the prepolymer with a second catalyst to carry out a vacuum polycondensation reaction to obtain a polyester.
[0041] The present invention has no particular limitation on the mixing order of the components in the reaction system, and the amount of each component used is based on the content of the structural units required by the product.
[0042] According to the present invention, the reaction conditions of each step may also adopt conventional conditions in the art.
[0043] Specifically, in step (1), the reaction conditions of the prepolymerization may include: reaction temperature of 190-250° C.; vacuum degree of 200-600 Pa; reaction time of 1-3 hours, or until the small molecules in the reaction system are almost exhausted and the fraction temperature remains unchanged.
[0044] In step (2), the reaction conditions of the vacuum polycondensation reaction may include: reaction temperature of 200-300° C.; vacuum degree of <300 Pa; and reaction time of 3-12 hours.
[0045] The present invention does not particularly limit the catalyst used in the polymerization reaction and its amount, and can be various conventional catalysts and conventional catalyst amounts for synthesizing polyester. The catalysts used in step (1) and step (2) can be the same or different. For example, the catalyst used in step (1) can be selected from at least one of compounds of metal titanium, antimony and tin; the catalyst used in step (2) can be selected from compounds of rare earth metal Ln and mixtures thereof, wherein the rare earth metal Ln is selected from at least one of lanthanide elements, scandium and yttrium.
[0046] According to the present invention, step (1) and step (2) can be carried out in the same reactor or in different reactors, that is, the prepolymer can be taken out and transferred to another reactor to continue the subsequent polymerization reaction.
[0047] According to the present invention, nitrogen is usually used as protection in the reaction system, but other atmospheres, including air, may also be used.
[0048] According to the second aspect of the present invention, the present invention provides a method for preparing the above-mentioned biodegradable polyester composition, which comprises: blending the components of the composition to obtain a mixture; extruding, cooling and pelletizing the mixture to obtain the biodegradable polyester composition.
[0049] In the present invention, operations such as blending and extrusion can be performed using common equipment and conventional parameters in the art. For example, the components can be added to a high-speed mixer for mixing; the mixed material can be added to a twin-screw extruder for extrusion.
[0050] The third aspect of the present invention provides a biodegradable non-woven fabric, which is prepared by using the above-mentioned biodegradable polyester composition.
[0051] According to the present invention, the nonwoven fabric is prepared by a spunbond method, and the device used can be a spunbond nonwoven fabric preparation device known in the art, and the preparation is performed using conventional process parameters. For example, the conditions of the spunbond method include: an extrusion temperature of 190-270°C, a web forming speed of 15-20m / min, and a hot rolling temperature of 100-110°C.
[0052] The substances and parameters not limited in the present invention can be selected according to the existing technology and belong to the conventional technical means in this field.
[0053] The present invention will be further described below with reference to the following examples, but is not limited to these examples.
[0054] In the following examples and comparative examples, the relevant raw materials and data were obtained by the following method:
[0055] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 40000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6 hours to obtain a polybutylene succinate / terephthalate product.
[0056] The polybutylene succinate / terephthalate copolymer has a molar fraction of 44% of the repeating unit (II) and a weight average molecular weight (Mw) of 35000 g / mol. The preparation method thereof comprises: adding 0.44 mol of terephthalic acid, 0.56 mol of succinic acid and 1.2 mol of 1,4-butanediol and 1 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1 mmol of a catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 5 hours to obtain a polybutylene succinate / terephthalate product.
[0057] The polybutylene succinate / terephthalate copolymer has a molar fraction of 42% of the repeating unit (II) and a weight average molecular weight (Mw) of 65000 g / mol. The preparation method thereof comprises: adding 0.42 mol of terephthalic acid, 0.58 mol of succinic acid and 1.2 mol of 1,4-butanediol and 1 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1 mmol of a catalyst Cat2 (lanthanum acetylacetonate), stirring and heating continuously, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8 hours to obtain a polybutylene succinate / terephthalate product.
[0058] The polybutylene succinate / terephthalate copolymer has a molar fraction of 46% of the repeating unit (II) and a weight average molecular weight (Mw) of 65000 g / mol. The preparation method thereof comprises: adding 0.46 mol of terephthalic acid, 0.54 mol of succinic acid and 1.2 mol of 1,4-butanediol and 1 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1 mmol of a catalyst Cat2 (lanthanum acetylacetonate), stirring and heating continuously, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8 hours to obtain a polybutylene succinate / terephthalate product.
[0059] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 40%, the weight average molecular weight (M w ) is 40000g / mol, and the preparation method thereof comprises: adding 0.4mol terephthalic acid, 0.6mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Adding 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continuing stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6 hours to obtain a polybutylene succinate / terephthalate product.
[0060] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 49%, the weight average molecular weight (M w ) is 40000g / mol, and the preparation method thereof comprises: adding 0.49mol terephthalic acid, 0.51mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6 hours to obtain a polybutylene succinate / terephthalate product.
[0061] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w) is 30000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 4.5 hours to obtain a polybutylene succinate / terephthalate product.
[0062] Polybutylene succinate / terephthalate copolymer, the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 65000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol succinic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 8 hours to obtain a polybutylene succinate / terephthalate product.
[0063] Poly (butylene adipate / terephthalate copolymer), the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 40000g / mol, and the preparation method thereof comprises: adding 0.47mol terephthalic acid, 0.53mol adipic acid and 1.2mol 1,4-butanediol, and 1mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2 hours). Add 0.1mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 6 hours to obtain a poly(adipate / butylene terephthalate) product.
[0064] Poly (sebacic acid / butylene terephthalate copolymer), the molar fraction of repeating unit (II) is 48%, the weight average molecular weight (M w) is 120000g / mol, and the preparation method thereof comprises: adding 0.48mol terephthalic acid, 0.52mol sebacic acid and 1.2mol 1,4-butanediol, and 0.8mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 10 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0065] Poly (sebacic acid / butylene terephthalate copolymer), the molar fraction of repeating unit (II) is 49%, the weight average molecular weight (M w ) is 105000g / mol, and the preparation method thereof comprises: adding 0.49mol terephthalic acid, 0.51mol sebacic acid and 1.2mol 1,4-butanediol, and 0.8mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 9 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0066] Poly (sebacic acid / butylene terephthalate copolymer), the molar fraction of repeating unit (II) is 49%, the weight average molecular weight (M w ) is 95000g / mol, and the preparation method thereof comprises: adding 0.49mol terephthalic acid, 0.51mol sebacic acid and 1.2mol 1,4-butanediol, and 0.8mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 8 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0067] Poly (butylene terephthalate / sebacic acid copolymer), the molar fraction of repeating unit (II) is 44%, the weight average molecular weight (M w) is 105000g / mol, and the preparation method thereof comprises: adding 0.44mol terephthalic acid, 0.56mol sebacic acid and 1.2mol 1,4-butanediol, and 0.8mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 9 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0068] Poly (butylene terephthalate / sebacic acid) copolymer, the molar fraction of repeating unit (II) is 40%, the weight average molecular weight (M w ) is 120000g / mol, and the preparation method thereof comprises: adding 0.4mol terephthalic acid, 0.6mol sebacic acid and 1.2mol 1,4-butanediol, and 0.8mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 10 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0069] The polybutylene sebacic acid / terephthalate copolymer has a molar fraction of 50% of the repeating unit (II) and a weight average molecular weight (Mw) of 120000 g / mol. The preparation method comprises: adding 0.5 mol of terephthalic acid, 0.5 mol of sebacic acid and 1.2 mol of 1,4-butanediol, and 0.8 mmol of a catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Adding 0.08 mmol of a catalyst Cat2 (lanthanum acetylacetonate), stirring and heating continuously, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 10 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0070] Poly (sebacic acid / butylene terephthalate copolymer), the molar fraction of repeating unit (II) is 48%, the weight average molecular weight (M w) is 80000g / mol, and the preparation method thereof comprises: adding 0.48mol terephthalic acid, 0.52mol sebacic acid and 1.2mol 1,4-butanediol, and 0.8mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 7.5 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0071] Poly (sebacic acid / butylene terephthalate copolymer), the molar fraction of repeating unit (II) is 48%, the weight average molecular weight (M w ) is 140000g / mol, and the preparation method thereof comprises: adding 0.48mol terephthalic acid, 0.52mol sebacic acid and 1.2mol 1,4-butanediol, and 0.8mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200Pa, collecting fractions, and reacting for about 15 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0072] Poly (sebacic acid / butylene terephthalate copolymer), the molar fraction of repeating unit (II) is 48%, the weight average molecular weight (M w ) is 100000 g / mol, and the preparation method thereof comprises: adding 0.48 mol terephthalic acid, 0.52 mol sebacic acid and 1.2 mol 1,4-butanediol, and 0.8 mmol catalyst Cat1 (tetrabutyl titanate) into a 1L reactor, protecting the system with nitrogen, stirring and heating, controlling the reaction temperature at 200-220°C, controlling the vacuum degree at about 400 Pa, collecting fractions, and collecting the fractions until the fractions are collected (about 2.5 hours). Add 0.08 mmol catalyst Cat2 (lanthanum acetylacetonate), continue stirring and heating, controlling the reaction temperature at 240-260°C, controlling the vacuum degree at about 200 Pa, collecting fractions, and reacting for about 8.5 hours to obtain a polybutylene sebacic acid / terephthalate product.
[0073] 1. The weight average molecular weight of the copolyester was determined by gel permeation chromatography (GPC). GPC used tetrahydrofuran as the mobile phase and polystyrene standard samples for calibration.
[0074] 2. The composition of the copolyester was determined by nuclear magnetic resonance (NMR) method. The NMR experiment was performed on an Agilent 600 MHz nuclear magnetic resonance instrument, the solvent was CDCl3, and the test temperature was room temperature.
[0075] 3. The tensile test was performed using an INSTRON-5965 tensile tester, INSTRON, USA.
[0076] Example 1
[0077] Biodegradable polyester composition: poly(butylene succinate / terephthalate) copolymer, NMR determination of the molar fraction of repeating unit (II) is 47%, the weight average molecular weight (M w ) is 40000 g / mol; poly (butylene sebacic acid / terephthalate copolymer, NMR determination of the molar fraction of repeating unit (II) is 48%, the weight average molecular weight (M w ) is 120000 g / mol; hindered phenol antioxidant 300; based on the total weight of poly(succinic acid / butylene terephthalate) copolymer and poly(sebacic acid / butylene terephthalate) copolymer, the content of poly(succinic acid / butylene terephthalate) copolymer is 20 weight%, and the content of poly(sebacic acid / butylene terephthalate) copolymer is 80 weight%; the content of hindered phenol antioxidant 300 is 2‰ of the total weight of poly(succinic acid / butylene terephthalate) copolymer and poly(sebacic acid / butylene terephthalate) copolymer.
[0078] The above components were pre-mixed with a high-speed mixer, and then extruded, cooled, and pelletized using a twin-screw extruder to obtain composition A1.
[0079] The above polymer A1 was dried at 60°C for 5 hours and then added to a spunbond nonwoven fabric processing equipment. The screw temperature of the spunbond equipment was set at 190-220°C, the web speed was 17m / min, and the hot rolling temperature was 105°C to obtain a nonwoven fabric B1. The performance parameters of the composition A1 and the nonwoven fabric B1 are shown in Table 1.
[0080] Example 2
[0081] Same as Example 1, the difference is: the mole fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 44%, and the weight average molecular weight (Mw) is 35000g / mol; the mole fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 49%, and the weight average molecular weight (Mw) is 105000g / mol. Based on the total weight of the polysuccinic acid / butylene terephthalate copolymer and the polysuccinic acid / butylene terephthalate copolymer, the content of the polysuccinic acid / butylene terephthalate copolymer is 10 weight %, and the content of the polysuccinic acid / butylene terephthalate copolymer is 90 weight %. Composition A2 and nonwoven fabric B2 are obtained, and the performance parameters are shown in Table 1.
[0082] Example 3
[0083] Same as Example 1, the difference is: the mole fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 42%, and the weight average molecular weight (Mw) is 65000g / mol; the mole fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 49%, and the weight average molecular weight (Mw) is 95000g / mol. Based on the total weight of the polysuccinic acid / butylene terephthalate copolymer and the polysuccinic acid / butylene terephthalate copolymer, the content of the polysuccinic acid / butylene terephthalate copolymer is 25 weight%, and the content of the polysuccinic acid / butylene terephthalate copolymer is 75 weight%. Composition A3 and nonwoven fabric B3 are obtained, and the performance parameters are shown in Table 1.
[0084] Example 4
[0085] Same as Example 1, the difference is: the mole fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 46%, and the weight average molecular weight (Mw) is 65000g / mol; the mole fraction of repeating unit (II) in the polysuccinic acid / butylene terephthalate copolymer is 44%, and the weight average molecular weight (Mw) is 105000g / mol. Based on the total weight of the polysuccinic acid / butylene terephthalate copolymer and the polysuccinic acid / butylene terephthalate copolymer, the content of the polysuccinic acid / butylene terephthalate copolymer is 25% by weight, and the content of the polysuccinic acid / butylene terephthalate copolymer is 75% by weight. Composition A4 and nonwoven fabric B4 are obtained, and the performance parameters are shown in Table 1.
[0086] Example 5
[0087] Same as Example 1, except that the molar fraction of the repeating unit (II) in the polybutylene succinate / terephthalate copolymer is 40%. Composition A5 and nonwoven fabric B5 were obtained, and their performance parameters are shown in Table 1.
[0088] Example 6
[0089] Same as Example 1, except that the molar fraction of the repeating unit (II) in the polybutylene succinate / terephthalate copolymer is 49%. Composition A6 and nonwoven fabric B6 were obtained, and their performance parameters are shown in Table 1.
[0090] Example 7
[0091] Same as Example 1, except that the molar fraction of the repeating unit (II) in the polysebacic acid / butylene terephthalate copolymer is 40%. Composition A7 and nonwoven fabric B7 are obtained, and their performance parameters are shown in Table 1.
[0092] Example 8
[0093] Same as Example 1, except that the molar fraction of the repeating unit (II) in the polysebacic acid / butylene terephthalate copolymer is 50%. Composition A8 and nonwoven fabric B8 are obtained, and their performance parameters are shown in Table 1.
[0094] Example 9
[0095] The same as Example 1, except that: based on the total weight of the poly(succinic acid / butylene terephthalate) copolymer and the poly(sebacic acid / butylene terephthalate) copolymer, the content of the poly(succinic acid / butylene terephthalate) copolymer is 3 wt %, and the content of the poly(sebacic acid / butylene terephthalate) copolymer is 97 wt %. Composition A9 and nonwoven fabric B9 were obtained, and the performance parameters were shown in Table 1.
[0096] Example 10
[0097] The same as Example 1, except that: based on the total weight of the poly(succinic acid / butylene terephthalate) copolymer and the poly(sebacic acid / butylene terephthalate) copolymer, the content of the poly(succinic acid / butylene terephthalate) copolymer is 30% by weight, and the content of the poly(sebacic acid / butylene terephthalate) copolymer is 70% by weight. Composition A10 and nonwoven fabric B10 were obtained, and the performance parameters were shown in Table 1.
[0098] Embodiment 11
[0099] Same as Example 1, except that the poly(succinic acid / butylene terephthalate) copolymer is replaced with a poly(adipate / butylene terephthalate) copolymer having a weight average molecular weight (Mw) of 40,000 g / mol. Composition A11 and nonwoven fabric B11 are obtained, and the performance parameters are shown in Table 1.
[0100] Comparative Example 1
[0101] The same as Example 1, except that: based on the total weight of the polybutylene succinate / terephthalate copolymer and the polybutylene sebacate / terephthalate copolymer, the content of the polybutylene succinate / terephthalate copolymer is 2 weight percent, and the content of the polybutylene sebacate / terephthalate copolymer is 98 weight percent. Composition CA1 and nonwoven fabric CB1 were obtained, and the performance parameters were shown in Table 1.
[0102] Comparative Example 2
[0103] The same as Example 1, except that: based on the total weight of the poly(succinic acid / butylene terephthalate) copolymer and the poly(sebacic acid / butylene terephthalate) copolymer, the content of the poly(succinic acid / butylene terephthalate) copolymer is 40% by weight, and the content of the poly(sebacic acid / butylene terephthalate) copolymer is 60% by weight. Composition CA2 and nonwoven fabric CB2 were obtained, and the performance parameters were shown in Table 1.
[0104] Comparative Example 3
[0105] Same as Example 1, except that the weight average molecular weight (M w ) is 30000 g / mol. Composition CA3 and nonwoven fabric CB3 were obtained, and the performance parameters are shown in Table 1.
[0106] Comparative Example 4
[0107] Same as Example 1, except that the weight average molecular weight (M w ) is 80000 g / mol. Composition CA4 and nonwoven fabric CB4 were obtained, and the performance parameters are shown in Table 1.
[0108] Comparative Example 5
[0109] Same as Example 1, except that the weight average molecular weight (M w ) is 140000 g / mol. Composition CA5 and nonwoven fabric CB5 were obtained, and the performance parameters are shown in Table 1.
[0110] Comparative Example 6
[0111] Same as Example 1, except that only poly(butylene succinate / terephthalate) copolymer was used, wherein the molar fraction of repeating unit (II) was 47%, and the weight average molecular weight (M w ) is 65000 g / mol. The nonwoven fabric was trial-produced. The performance parameters are shown in Table 1.
[0112] Comparative Example 7
[0113] Same as Example 1, except that only poly(sebacic acid / butylene terephthalate) copolymer was used, wherein the molar fraction of repeating unit (II) was 48%, and the weight average molecular weight (M w ) is 100000 g / mol. The nonwoven fabric was trial-produced. The performance parameters are shown in Table 1.
[0114] Table 1
[0115]
[0116]
[0117] As can be seen from Table 1, the biodegradable nonwoven fabric of the present invention has good processability and mechanical properties. The nonwoven fabric has high elongation, high toughness, and also has a certain rigidity, which ensures durability and strength. The present invention provides a simple and easy method, which can adjust the material composition by mechanical blending to obtain excellent and adjustable mechanical properties. The combination of polyesters with different molecular weights, on the one hand, ensures processability, and on the other hand, makes the prepared nonwoven fabric have excellent comprehensive properties.
[0118] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A biodegradable polyester composition, characterized in that: The composition contains aliphatic-aromatic copolyester A and aliphatic-aromatic copolyester B, wherein the content of aliphatic-aromatic copolyester A is 3-30% by weight and the content of aliphatic-aromatic copolyester B is 70-97% by weight based on the total weight of aliphatic-aromatic copolyester A and aliphatic-aromatic copolyester B; The aliphatic-aromatic copolyester A is a copolymer containing repeating units represented by formula (I) and (II); In formula (I), m1=4, n1=2 or 4; In the aliphatic-aromatic copolyester A, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 40-49 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester A is 35000 g / mol-65000 g / mol; The aliphatic-aromatic copolyester B is a copolymer containing repeating units represented by formula (III) and (II); In formula (III), m2=4, n2=8; In the aliphatic-aromatic copolyester B, based on the total molar number of repeating units represented by formulas (III) and (II), the content of the repeating unit represented by formula (II) is 40-50 mol%; the weight average molecular weight of the aliphatic-aromatic copolyester B is 95000 g / mol-120000 g / mol.
2. The biodegradable polyester composition according to claim 1, wherein Based on the total weight of aliphatic-aromatic copolyester A and aliphatic-aromatic copolyester B, the content of aliphatic-aromatic copolyester A is 10-25% by weight, and the content of aliphatic-aromatic copolyester B is 75-90% by weight.
3. The biodegradable polyester composition according to claim 1, wherein In the aliphatic-aromatic copolyester A, based on the total molar number of the repeating units represented by formula (I) and (II), the content of the repeating unit represented by formula (II) is 42-47 mol%.
4. The biodegradable polyester composition according to claim 1, wherein In the aliphatic-aromatic copolyester B, based on the total molar number of the repeating units represented by formula (III) and (II), the content of the repeating unit represented by formula (II) is 44-49 mol%.
5. The biodegradable polyester composition according to claim 1, wherein The weight average molecular weight of the composition is 88000-115000 g / mol.
6. The biodegradable polyester composition according to claim 1, wherein The composition further contains an auxiliary agent, which is selected from at least one of an antioxidant, a chain extender and talc.
7. The method for preparing the biodegradable polyester composition according to any one of claims 1 to 6, characterized in that: The preparation method comprises: blending the components of the composition to obtain a mixed material; and extruding, cooling and pelletizing the mixed material to obtain the biodegradable polyester composition.
8. A biodegradable nonwoven fabric, characterized in that: The nonwoven fabric is prepared by using the biodegradable polyester composition described in any one of claims 1 to 6.
9. The biodegradable nonwoven fabric according to claim 8, wherein: The nonwoven fabric is produced by a spunbond method.
10. The biodegradable nonwoven fabric according to claim 9, wherein: The conditions of the spunbond method include: an extrusion temperature of 190-270°C, a web forming speed of 15-20 m / min, and a hot rolling temperature of 100-110°C.
Citation Information
Patent Citations
Biodegradable nonwoven fabric and fiber product using the same
CN102395720A
Cited By
Degradable green sludge dewatering drain board
CN121609492A
Degradable green sludge dewatering drainage plate
CN121609492B